Case report: Sequential treatment strategy for advanced basal cell carcinoma in Gorlin-Goltz syndrome: integration of vismodegib, radiotherapy, surgery, and high-intensity focused ultrasound - Calik, Jacek; Oślizło, Małgorzata; Słocka-Romaniuk, Beata; Elsaftawy, Ahmed; Sauer, Natalia (Frontiers in Oncology, 2024)
Managing advanced basal cell carcinoma (BCC) in patients with Gorlin-Goltz syndrome presents unique clinical challenges due to the tumor's aggressive nature and potential for widespread metastasis. This case study details a sequential treatment regimen for a 68-year-old female patient with an extensive, inoperable BCC. Employing a multimodal approach that integrates radiotherapy, the Hedgehog pathway inhibitor vismodegib, and High-Intensity Focused Ultrasound (HIFU), we demonstrate the potential for nearly complete remission in a patient with advanced BCC. Initial treatment with radiotherapy and vismodegib reduced tumor size significantly, but the largest mass displayed resistance over time, signifying the need for innovative therapies. Subsequent HIFU treatment targeted individual lesions, showcasing a non-invasive method that provided precise treatment while mitigating systemic side effects. The case emphasizes the necessity of continual adaptation in treatment plans to address the development of resistance and underscores the importance of incorporating new technologies and targeted therapies for complex BCC cases. The successful outcome of this integrated strategy suggests a promising direction for future research and highlights the importance of multidisciplinary approaches that tailor treatment to individual patient needs, tumor characteristics, and evolving therapeutic landscapes.